2008
DOI: 10.1074/jbc.m803819200
|View full text |Cite
|
Sign up to set email alerts
|

Selective Roles for Cholesterol and Actin in Compartmentalization of Different Proteins in the Golgi and Plasma Membrane of Polarized Cells

Abstract: To determine the roles of cholesterol and the actin cytoskeleton in apical and basolateral protein organization and sorting, we have performed comprehensive confocal fluorescence recovery after photobleaching analyses of apical and basolateral and raft-and non-raft-associated proteins, both at the plasma membrane and in the Golgi apparatus of polarized MDCK cells. We show that at both the apical and basolateral plasma membrane domains, raft-associated proteins diffuse faster than non-raftassociated proteins an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 50 publications
6
63
0
Order By: Relevance
“…Consistent with this hypothesis, we had previously shown that a double point mutation in the GFP sequence (S49/71) that prevents GFP dimerization also impairs oligomerization in the Golgi and the consequent apical sorting of the protein 11 . Taken together these data indicate that also in the Golgi of epithelial cells the capacity of dimerization is required for the construction of cholesterol-dependent higher order molecular organization of GPI-APs 26,27 .…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Consistent with this hypothesis, we had previously shown that a double point mutation in the GFP sequence (S49/71) that prevents GFP dimerization also impairs oligomerization in the Golgi and the consequent apical sorting of the protein 11 . Taken together these data indicate that also in the Golgi of epithelial cells the capacity of dimerization is required for the construction of cholesterol-dependent higher order molecular organization of GPI-APs 26,27 .…”
Section: Discussionmentioning
confidence: 54%
“…Because in polarized MDCK cells cholesterol is a key regulator of the Golgi homo-clustering of apical GPI-APs 11,26,27 we asked whether differences in the cellular content of cholesterol between polarized and non-polarized cells could explain the different organization of GPI-APs at the cell surface. To address this we analyzed the B of GFP-FR in non-polarized MDCK cells following exogenous addition of cholesterol ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These data can be explained in at least two different ways: Either, the addition of cholesterol stabilises the interaction between the basolateral GPI-AP and lipid rafts (i.e. by rigidifying the raft membranes or interfering with the free diffusion of proteins) (Lebreton et al, 2008), thus allowing the stabilisation of the protein in rafts and consequently its oligomerisation and apical sorting; or, cholesterol addition may change the characteristics of the surrounding lipid environment (i.e. conversion of basolateral rafts to apical rafts), thus enabling the protein originally associated with the basolateral raft to oligomerise and to be delivered apically.…”
Section: Addition Of Cholesterol Results In Gfp-prp Oligomerisation Amentioning
confidence: 99%
“…associated proteins ( 45 ). However, it is not known how factors, such as membrane domain heterogeneity, TGN membrane continuity, or possible changes to PI4KII ␣ lateral diffusion, might contribute to the cholesterolsensitivity of the enzyme.…”
mentioning
confidence: 99%